Convection heat transfer enhancement by inserting a concentric tube into an externally heated tube and controlling the concurrent flow rates of a phase change nanofluid and water. (15th December 2022) - Ho, C.J.; Kung, X.Y.; Lai, Chi-Ming
Abstract: To effectively improve internal convection, in this study, the heat transfer enhancement using concurrent forced flows of phase change nanofluids/water through the outer ring/inner tube of a double tube was investigated experimentally and compared to that of an identical tube filled with water, for which limited information is available. The parameters are described as follows: heating powers of 70, 110, and 150 W; mass fractions of the phase change nanofluid of 2.04 %, 2.91 %, and 7.11 %; flow ratios of 0.33–4.0; and a total flow rate of 304 cm 3 /min. The results indicated that the PCM concentration, flow ratio, and heating power must be correctly matched so that the phase change in the working fluid falls in the expected position and the effect of the latent heat can be fully realized. For a 2.04 % PCM emulsion, when the heating wattage is 70 W and the flow ratio is approximately intermediate (0.51), the local heat transfer effectiveness of the heated section is >1, indicating that using a PCM emulsion as the working fluid instead of water can effectively increase the heat transfer rate. Highlights: A smaller tube was inserted in an externally heated tube to form a concentric double tube. Outer annulus/inner tube are filled with PCM nanofluid/water. Forced convective heat transfer of the laminar flow was experimentally investigated. Functional fluids and adequate concurrent flow ratios enhance the convective heat transfer.